Determination of hydrocarbon sources in major rivers and estuaries of peninsular Malaysia using aliphatic hydrocarbons and hopanes as biomarkers. Issue 3 (14th July 2022) - Keshavarzifard, Mehrzad; Zakaria, Mohamad Pauzi; Sharifinia, Moslem; Grathwohl, Peter; Keshavarzifard, Shahin; Sharifi, Reza; Abbasi, Sajjad; Mehr, Meisam Rastegari
Abstract: In this study, levels and sources of aliphatic hydrocarbons and hopanes in surface sediments collected from rivers and estuaries of Peninsular Malaysia were assessed. The concentrations of total n -alkanes ranged from 21.19 to 364.54, and the concentrations of hopanes ranged from 0.23 to 2.45 mg kg −1 dry weight. Evaluation of aliphatic diagnostic indices including Carbon Preference Index (CPI), low molecular weight/high molecular weight ratio (LMW/HMW), terrigenous to aquatic ratio (TAR), carbon preference index (CPI), average chain length (ACL) and pristine to phytane indicate mostly petrogenic input especially in estuaries, which is indicative of anthropogenic activities in the study areas. The results also indicate biogenic origin n -alkanes masked by the anthropogenic features in some stations. The hopane ratios indicate hopanes from the Prai and Malacca Rivers were similar to Middle East Crude Oil (MECO), indicating MECO as one of the sources of petroleum hydrocarbons.